Independent association of weight-adjusted waist index with asthma in U.S. adolescents: Mediating roles of eosinophil percentage, total cholesterol, and HDL cholesterol. - Lei He; Yingxia Deng; Xiaohua Liu; Yao Wang; Jing Tang (PLoS ONE)
Background Obesity is a risk factor for asthma in adolescents. "Although body mass index (BMI) is the most widely used metric for assessing obesity, it has several limitations. The weight-adjusted waist index (WWI) is a novel central obesity indicator and accurately reflects body composition. We aimed to explore the association of WWI with asthma in adolescents using NHANES 1999-2020 data. Methods WWI was calculated based on waist circumference (cm) divided by the square root of weight (kg). Current asthma status in adolescents was determined based on participants' self-reports. Multivariate logistic regression analysis, restricted cubic spline (RCS) analysis, mediation analysis, and stratified analysis were used to comprehensively explore this association. Results A total of 15,796 adolescents were included. In the fully adjusted model, WWI was positively associated with current asthma in adolescents (odds ratio 1.252, 95% confidence interval 1.125-1.392, p = 0.0001). Participants in the highest WWI quartile (Q4) showed a 54.5% higher prevalence of asthma compared to Q1 (p for trend = 0.0007).. RCS modeling indicated that the association was linear. Mediation analyses indicated that blood eosinophil percentage (EOS%), total cholesterol (TC), and high-density lipoprotein cholesterol (HDL-C) partially mediated this association by 9.89% (p < 0.0001), 7.47% (p = 0.048), and 8.24% (p = 0.044), respectively. This association was independent of BMI, and BMI also did not significantly interact with this association (p for interaction = 0.682). Conclusions WWI was linearly and positively associated with the prevalence of current asthma among U.S. adolescents, independently of BMI. EOS%, TC, and HDL-C partially mediated this association.